Long Term Causality of GDP led Export (GLE) using VECM Model with Reference to India - Joshi, Amitabh (Asian Accounting and Auditing Advancement, 2014)
The aim of this paper is to study the long term and short-term relationship between GDP and Export. Various statistical tests like Johansen Cointegration Test, Vector Error Correction Estimates, Wald test, ARCH Test, and Serial Correlation Test have been performed. The data was collected from the website of the World Bank for a period of 41 years i.e. 1970 to 2011. It was observed that the data shows cointegration between the variables but a long-term association was not found.